Introduction and feeding practices of solid food in preterm infants born in Salzburg! - Edda Hofstätter; Verena Köttstorfer; Patricia Stroicz; Sebastian Schütz; Lorenz Auer-Hackenberg; Johannes Brandner; Martin Wald (BMC, 2021)
Abstract Background It is shown that meeting the increased nutritional demand of preterm infants from birth is not only important for survival but essentially contributes to the infants` overall development and long-term health. While there are established guidelines for weaning term infants, evidence regarding preterm infants is scarce and less precise. The aim of this study was to identify the current practices on introducing solids to preterm infants amongst caregivers in Salzburg and determine potential reasons for early weaning. Methods Altogether 68 infants born between 24 0/7 and 36 6/7 weeks were recruited and detailed structured interviews with the caregivers were conducted at 17 weeks corrected age. Weight, height and head circumference were collected. Results 52% of the study group received solids before the recommended 17 weeks corrected age. For this group the mean age being 13.77 ± 1.11 weeks corrected age. Premature introduction of solids significantly correlates with exclusively and early formula-feeding. 34% were weaned due to recommendation by their paediatrician. 23% of the preterm infants even received solids before 12 weeks corrected age, putting them at risks for developing obesity, celiac disease and diabetes. Conclusions This study shows the necessity for clear guidelines regarding the introduction of complementary feeding in preterm infants as well as the importance of their implementation. Caregivers should receive information on this topic early enough and they should fully understand the difference between chronological and corrected age.